Phytochemical-assisted green synthesis of CuFeOx nano-rose electrocatalysts for oxygen evolution reaction in alkaline media - Sarkar D.K.; Selvanathan V.; Mottakin M.; Hasan A.K.M.; Islam M.A.; Almohamadi H.; Alharthi N.H.; Akhtaruzzaman M. (Royal Society of Chemistry, 2024)
This study represents a green synthesis method for fabricating an oxygen evolution reaction (OER) electrode by depositing two-dimensional CuFeOx on nickel foam (NF). Two-dimensional CuFeOx was deposited on NF using in situ hydrothermal synthesis in the presence of Aloe vera extract. This phytochemical-assisted synthesis of CuFeOx resulted in a unique nano-rose-like morphology (petal diameter 30-70 nm), which significantly improved the electrochemical surface area of the electrode. The synthesized electrode was analyzed for its OER electrocatalytic activity and it was observed that using 75% Aloe vera extract in the phytochemical-assisted synthesis of CuFeOx resulted in improved OER electrocatalytic performance by attaining an overpotential of 310 mV for 50 mA cm?2 and 410 mV for 100 mA cm?2. The electrode also sustained robust stability throughout the 50 h of chronopotentiometry studies under alkaline electrolyte conditions, demonstrating its potential as an efficient OER electrode material. This study highlights the promising use of Aloe vera extract as a green and cost-effective way to synthesize efficient OER electrode materials. 2023 The Royal Society of Chemistry.